A PEX7-centered perspective on the peroxisomal targeting signal type 2-mediated protein import pathway - Rodrigues, TA (2014)
Peroxisomal matrix proteins are synthesized on cytosolic ribosomes and transported to the organelle by shuttling receptors. Matrix proteins containing a type 1 signal are carried to the peroxisome by PEX5, whereas those harboring a type 2 signal are transported by a PEX5-PEX7 complex. The pathway followed by PEX5 during the protein transport cycle has been characterized in detail. In contrast, not much is known regarding PEX7. In this work, we show that PEX7 is targeted to the peroxisome in a PEX5- and cargo-dependent manner, where it becomes resistant to exogenously added proteases. Entry of PEX7 and its cargo into the peroxisome occurs upstream of the first cytosolic ATP-dependent step of the PEX5-mediated import pathway, i.e., before monoubiquitination of PEX5. PEX7 passing through the peroxisome becomes partially, if not completely, exposed to the peroxisome matrix milieu, suggesting that cargo release occurs at the trans side of the peroxisomal membrane. Finally, we found that export of peroxisomal PEX7 back into the cytosol requires export of PEX5 but, strikingly, the two export events are not strictly coupled, indicating that the two proteins leave the peroxisome separately.